Validation of the Hingmed WBP-02A device for ambulatory blood pressure monitoring according to the European Society of Hypertension International Protocol revision 2010. Issue 3 (June 2019) - Fania, Claudio; Vezzù, Leonardo; Lazzaretto, Ilaria; Palatini, Paolo
Abstract : The objective of this study was to determine the accuracy of the Hingmed WBP-02A device for ambulatory blood pressure (BP) monitoring according to the International Protocol of the European Society of Hypertension (ESH-IP). Device evaluation was carried out in 33 patients. The mean age was 69.8±13.8 years, the mean systolic BP was 137.6±27.0 mmHg (range: 96–172), the mean diastolic BP was 86.7±20.1 mmHg (range: 48–124) and the mean arm circumference was 30.1±6.2 cm (range: 20–43). The protocol requirements were followed precisely. Four different cuffs, small, standard, large, and extra-large were used. The device comfortably passed all ESH-IP requirements, as 84 out of 99 device–observer systolic BP differences and 97 of 99 diastolic BP differences were within ±5 mmHg thereby fulfilling the standards of the protocol. Device–observer BP differences were unrelated to arm circumference. These data show that the Hingmed WBP-02A device for ambulatory BP monitoring met the requirements for validation by the ESH-IP and can be recommended for clinical use in the adult population.